O ensino da álgebra no 8º ano do ensino fundamental: compreendendo algumas das dificuldades apresentadas pelos alunos por meio da análise da resolução de exercícios - Souza, Sandra Brito de (2019)
This study aimed to investigate the real difficulties presented by elementary school students in solving algebraic exercises. It was sought through a qualitative approach, to observe and analyze the nature of the errors committed by 20 students of the 8th grade of Elementary School when solving some exercises related to the subject. The methodological procedures used in the research were based on the application of 5 exercises and observations. For theoretical background, David Paul Ausubel Theory of Significant Learning was chosen. The investigation showed that the non-appropriation of certain previous knowledge in mathematics impaired the resolution of the exercises. The students' difficulties, according to the research, lie in exercises involving knowledge beyond algebra. It is hoped that an investigation with these characteristics may highlight the relevance of some important prior knowledge to the process of meaningful learning in algebra and thus contribute to broaden the understanding of the student's teaching and learning process.